2022
DOI: 10.1093/schbul/sbac099
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Controlled Trial of the Effects of Early Intervention Services On Insight in First Episode Psychosis

Abstract: Background and Hypothesis Impaired insight into one’s illness is common in first episode psychosis (FEP), is associated with worse symptoms and functioning, and predicts a worse course of illness. Despite its importance, little research has examined the effects of early intervention services (EIS) on insight. Designs This paper evaluated the impact of EIS (NAVIGATE) on insight compared to usual community care (CC) in a large … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 64 publications
0
1
1
Order By: Relevance
“…It is important to note that other studies have also failed to demonstrate a significant relationship between insight and depression at Previous findings (Crumlish et al, 2005;DeTore et al, 2022), together with the findings of the current study, raise questions regarding the importance of insight in depression during this phase of illness. It is possible that over time and with early intervention, the negative effects of insight on depression begin to wane and insight no longer affects depression.…”
Section: Discussioncontrasting
confidence: 46%
See 1 more Smart Citation
“…It is important to note that other studies have also failed to demonstrate a significant relationship between insight and depression at Previous findings (Crumlish et al, 2005;DeTore et al, 2022), together with the findings of the current study, raise questions regarding the importance of insight in depression during this phase of illness. It is possible that over time and with early intervention, the negative effects of insight on depression begin to wane and insight no longer affects depression.…”
Section: Discussioncontrasting
confidence: 46%
“…Crumlish et al, 2005 ). Interestingly, in a recent RCT on the effects of early intervention for first episode psychosis on insight, DeTore et al ( 2022 ) found the presence of the insight–depression paradox in the whole sample at baseline. However, at 6 months follow‐up, there was no association between insight and depression among individuals who participated in the early intervention, indicating that early intervention might reduce the insight–depression paradox.…”
Section: Discussionmentioning
confidence: 99%